2000
DOI: 10.1038/sj.ijo.0801290
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of somatotroph cell function by the adipose tissue

Abstract: Obese subjects exhibit a marked decrease in plasma growth hormone (GH) levels. However, the mechanisms by which increased adiposity leads to an impairment of GH secretion are poorly understood. Recent evidence suggests that the adipose tissue can markedly in¯uence GH secretion via two different signals, namely free fatty acids (FFA) and leptin. FFA appear to inhibit GH secretion mainly by acting directly at pituitary level. Interestingly, reduction in circulating FFA levels in obese subjects led to a marked in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
1
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 12 publications
0
21
1
1
Order By: Relevance
“…8,30,34 Stimulatory role of leptin in the regulation of rat somatotroph function has been shown; in fact, fasting inhibits GH secretion and leptin restores it. 9,11 However, in humans fasting stimulates GH while inhibiting leptin levels 31 and the fasting-induced leptin decrease is more marked in normal than in obese subjects. 35 Thus, the lack of GH response to fasting in obesity is unlikely to reflect leptinmediated mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…8,30,34 Stimulatory role of leptin in the regulation of rat somatotroph function has been shown; in fact, fasting inhibits GH secretion and leptin restores it. 9,11 However, in humans fasting stimulates GH while inhibiting leptin levels 31 and the fasting-induced leptin decrease is more marked in normal than in obese subjects. 35 Thus, the lack of GH response to fasting in obesity is unlikely to reflect leptinmediated mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…The chronic elevation of circulating FFA levels, which were further enhanced by fasting, could also have a key role in counteracting the GH response to starvation in obesity. 10,11,29 FFA has a strong inhibitory action on somatotroph secretion acting at either the pituitary or the hypothalamic level; 31,32,36 in fact, lipolysis inhibitors restore GH secretion in obesity. 10,11,29,37 In the absence of any significant increase in GH secretion obese patients in our study showed normal activation of lipolysis; this probably reflects the fasting-induced response of other contraregulatory hormones.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…NPY inhibits GH secretion, [36], but leptin, in physiological conditions, by inhibiting somatostatin release and stimulating GHRH (Growth hormone releasing hormone) secretion, stimulates GH [2]. Excess of growth hormone decreases leptin blood concentration [3].…”
Section: Introductionmentioning
confidence: 99%